The Effects of Exogenous Salicylic Acid on Endogenous Phytohormone Status in Hordeum vulgare L. under Salt Stress - Torun, Hülya; Novák, Ondřej; Mikulík, Jaromír; Strnad, Miroslav; Ayaz, Faik Ahmet (Plants (Basel, Switzerland), 2022)
Acclimation to salt stress in plants is regulated by complex signaling pathways involving endogenous phytohormones. The signaling role of salicylic acid (SA) in regulating crosstalk between endogenous plant growth regulators' levels was investigated in barley (Hordeum vulgare L. 'Ince'; 2n = 14) leaves and roots under salt stress. Salinity (150 and 300 mM NaCl) markedly reduced leaf relative water content (RWC), growth parameters, and leaf water potential (LWP), but increased proline levels in both vegetative organs. Exogenous SA treatment did not significantly affect salt-induced negative effects on RWC, LWP, and growth parameters but increased the leaf proline content of plants under 150 mM salt stress by 23.1%, suggesting that SA enhances the accumulation of proline, which acts as a compatible solute that helps preserve the leaf's water status under salt stress. Changes in endogenous phytohormone levels were also investigated to identify agents that may be involved in responses to increased salinity and exogenous SA. Salt stress strongly affected endogenous cytokinin (CK) levels in both vegetative organs, increasing the concentrations of CK free bases, ribosides, and nucleotides. Indole-3-acetic acid (IAA, auxin) levels were largely unaffected by salinity alone, especially in barley leaves, but SA strongly increased IAA levels in leaves at high salt concentration and suppressed salinity-induced reductions in IAA levels in roots. Salt stress also significantly increased abscisic acid (ABA) and ethylene levels; the magnitude of this increase was reduced by treatment with exogenous SA. Both salinity and SA treatment reduced jasmonic acid (JA) levels at 300 mM NaCl but had little effect at 150 mM NaCl, especially in leaves. These results indicate that under high salinity, SA has antagonistic effects on levels of ABA, JA, ethylene, and most CKs, as well as basic morphological and physiological parameters, but has a synergistic effect on IAA, which was well exhibited by principal component analysis (PCA).
Keywords: Hordeum vulgare; salicylic acid; barley; salt stress; phytohormones